Leveraging international R&D teams of portfolio entrepreneurs and management controllers to innovate: Implications of algorithmic decision-making - Rodgers Waymond; William Y. Degbey William Y.; Söderbom Arne; Leijon Svante (Elsevier, 2022)
We focus on how international research and development (R&D) teams of portfolio entrepreneurs and their
management controllers can help to innovate and sustain entrepreneurial activities. An algorithmic decision-making model is implemented that indicates how such portfolio entrepreneurs build complex business structures and create a context for management accounting controllers’ information that is suggestive of R&D
internationalization challenges. A case study is utilized to compare one large and one medium-sized business
conglomerate. Open interviews were conducted with portfolio entrepreneurs and their management controllers. We found that the international R&D teams of portfolio entrepreneurs and their management controllers have different mindsets when assessing sustainable innovative approaches for the existing business and for future expansion through acquisitions. Our findings assert the importance of context when understanding the challenges of management controllers dealing with the internationalization of such R&D efforts.